Vertical distribution of Fe, P and correlation with organic carbon in coastal sediments of Yellow Sea, Eastern China - Qi, Zizhen; Gao, Lei; Chen, Daixing; Wang, Xuhao; Liu, Huan; Yang, Yang; Zhao, Yulian; Lu, Xiancai (Frontiers in Marine Science, 2023)
The coastal zone is considered as a major carbon pool. Iron minerals and phosphates are vital factors affecting the amounts and occurrence of total organic carbon (TOC) in sediments. However, coupling mechanisms of iron (Fe) and phosphorous (P) in the source-sink transition of TOC in coastal sediments is poorly understood. This study characterized the distribution of Fe, P and TOC contents of three independent 170 cm sediment cores sampled from a coastal aquaculture area in the eastern Jiangsu Province, and quantified the correlations among Fe, P, median grain diameter (Dx(50)), and TOC. The results showed total phosphorus (TP) content ranges in a scope of 337.4-578.0 mg/kg, and many depths recorded moderate P eutrophication. Inorganic phosphorus (DA + IP) and biogenic apatite were the primary components of TP, accounting for 25.19–55.00 and 26.71–49.62%, respectively. The Fe contents varied from 987.9 mg/kg to 2900.7 mg/kg, in which oxidized iron (Feox) accounted for about 62.2–79.4%. In the vertical profile, the TOC was positively correlated with the contents of low-crystallinity Fe-bearing carbonates (Fecarb), high crystallinity pyrite (FePy), iron-bound phosphorus (PCDB), manganeses (Mn), and nitrogen (N), while it was negatively correlated with DA + IP, organic phosphorus (OP), and Dx(50). Based on the the partial least squares (PLS) model, we proposed that the higher FePy, Mn, magnetite (FeMag), Fecarb, PCDB, amorphous exchangeable Fe (Ex-Fe), and authigenic apatite phosphorus (Bio-P) in sediments represent the high capacity for TOC sink, whereas, higher DA + IP, and OP indicate a TOC conversion to the source. The non-siginificat indication of Feox on TOC source-sink is due to its surplus and strong reactivity relative to TOC content. These revealed correlations provide a theoretical reference for understanding and regulating the burial rate and storage of TOC by changing the input of Fe minerals and P components into coastal sediments.